ANALISA IMPLEMENTASI PROGRAM POLISI RW DALAM MENDUKUNG HARKAMTIBMAS DI WILAYAH HUKUM POLRES METRO BEKASI KOTA - Krisnawan, Hendra; Lubis, Rahmadsyah (Jurnal Ilmu Kepolisian, 2024)
This research was initiated by thinking about the RW Police program, which is actually a program needed by the community, but in reality it has not been implemented optimal. This is shown by the high number of crimes and violations that occur in the Bekasi City Metro Police jurisdiction when compared between before the RW Police Program (in 2021 and 2022) and after the implementation of the RW Police Program (in 2023). On the other hand, the concept of the RW Police program, which facilitates one RW with one police officer who lives in the RW, is a good program because with this concept it is hoped that the police in each RW can get to know more and be closer to the community so that they can become partners in creating public security. So, in order to maximize the implementation of the RW Police program, it is necessary to develop the right strategy and equip RW Police officers in the field with good problem-solving skills in order to maximize partnerships with the community and support the creation of security, especially in the Bekasi Metro Police jurisdiction. This research was conducted using a qualitative method with a constructivism paradigm where the author wanted to seek an in-depth understanding of the implementation of the RW Police in supporting the security forces in the jurisdiction of the Bekasi Metro Police, find obstacles in the field and find the right strategy to maximize its implementation.